2022
DOI: 10.1186/s13613-022-00984-z
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine does not improve valproic acid poisoning management: a cohort study with toxicokinetics and concentration/effect relationships

Abstract: Background Valproic acid (VPA) poisoning is responsible for life-threatening neurological and metabolic impairments. Despite only low-level evidence of effectiveness, L-carnitine has been used for years to prevent or reverse VPA-related toxicity. We aimed to evaluate the effects of L-carnitine used to treat acute VPA poisoning on the time-course of plasma VPA concentrations and VPA-related toxicity. We designed a single-center cohort study including all VPA-poisoned patients admitted to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Time to onset of hyperammonaemia was not limited to the introduction period in the first few days following the liable drug start and could be delayed. Several mechanisms might explain this delayed reaction that has also been found in previous studies [ 16 , 28 , 29 ]. First, it cannot be ruled out that hyperammonaemia is a dose-dependent adverse effect occurring at a "supratherapeutic" cumulative dose for some medications such as chemotherapies.…”
Section: Discussionsupporting
confidence: 76%
“…Time to onset of hyperammonaemia was not limited to the introduction period in the first few days following the liable drug start and could be delayed. Several mechanisms might explain this delayed reaction that has also been found in previous studies [ 16 , 28 , 29 ]. First, it cannot be ruled out that hyperammonaemia is a dose-dependent adverse effect occurring at a "supratherapeutic" cumulative dose for some medications such as chemotherapies.…”
Section: Discussionsupporting
confidence: 76%
“…Based on this potential risk, carnitine therapy should be avoided during acute metabolic disorders ( Spiekerkoetter et al, 2009 ). Although carnitine supplementation has been widely used to prevent and treat fatty liver toxicity caused by VPA, recent studies have shown that carnitine supplementation has a minimal therapeutic effect in patients with acute toxicity caused by VPA( Nguyen et al, 2022 ). On the other hand, since carnitine supplementation may increase ACs accumulation, the search for a potential protective agent against VPA-induced hepatotoxicity that both upregulates fatty acid β-oxidation in mitochondria and does not cause ACs accumulation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature is mixed on the efficacy of using L-carnitine for acute toxicity. Nguyen et al note that while L-carnitine reduces peak serum lactate levels in acute valproate toxicity, it does not speed up the return of blood lactate to normal levels nor help in valproate clearance [12], meaning that L-carnitine may help reduce the extent of organ damage in severe valproate toxicity, but may not improve prognosis and length of hospital stay.…”
Section: Current Literature On Treating Valproate Toxicitymentioning
confidence: 99%